Does the Learning Environment Affect Students' Mathematics Achievement? - AlAyyubi, IbnuImam; Nurfajriyah, DewiSyifa; Nurhikmah, Nurhikmah; Prayetno, Eko; Yumna, Hanin (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to describe the relationship and causal effects between independent and dependent variables, namely the Learning Environment and Students' Mathematics Achievement, using a causal-correlational study at SDN 074 Ayudia, Bandung City, with a population of all students and a sample of 28 students from class VB. This study uses a quantitative research method with an explanatory research approach. The sampling technique employed was probability sampling using simple random sampling, while the instruments used were questionnaires and tests. The analysis requirements for the data used include normality testing using the Kolmogorov-Smirnov test and linearity testing, with hypotheses involving correlation and regression analysis assisted by SPSS version 26. Based on the research results, it can be concluded that the Learning Environment has a significant influence on Students' Mathematics Achievement. The normality test results indicate that the data is normally distributed, thus meeting the requirements for further statistical analysis.